Comparing structure and organisation of development bureaucracies in Europe: a pilot study of European aid administrations - Thomas Henökl (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
In Europe, current efforts of achieving “policy coherence” and adopting “whole of government” or “joined-up” responses to global crises increasingly involve and entwine both the national and the European Union (EU) levels in the common performance of tasks. To better understand these emerging networks or “administrative spaces”, we need to study the reform and reorganisation of the multi-layer governmental structures and capacities entrusted with the design and implementation of such common strategies. Whereas existing literature frequently focusses on the institutional context and actor constellations at the political level, the emphasis of this study is put on the organisational structure, interaction patterns and the particular roles of decision-makers within public administrative bodies to identify and explain goal conflicts, diverging preferences and variation in administrative decision behaviour. Empirically, the paper is directed towards developing the framework for a two-dimensional network analysis of national and EU-level development bureaucracies, looking at: the structure and organisation of member states' ministries/agencies dealing with foreign aid and cooperation; how these entities prioritise and allocate attention and resources; in which ways they connect and communicate among themselves; how they interact with other national government departments; as well as the different hierarchical layers within the EU's multi-level administration, within international bureaucracies and in emerging global governance structures (United Nations system, etc.). The aspect that is under particular scrutiny are the cross-cutting vertical–horizontal links between administrative hierarchies that, in a reiterated and parallel manner, contribute to the specific network character of European foreign and development policy. Preliminary findings point towards higher degrees of cross-sectoral whole-of-government approaches, increased tendencies towards central steering facilitating coordination between hierarchical levels, use of new instruments and strengthened private-sector involvement. The detected trend appears to be an international movement of integrating aid administrations into the wider foreign policy area as well as to more closely cooperate with other domestic policy departments.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik